PENGARUH EARNING PER SHARE, RETURN ON ASSET, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PT. INDOCEMENT TUNGGAL PRAKARSA, Tbk PERIODE 2021-2023 - Benedikta Olga Pauta; Grace Sriati Mengga; Yohanis Lotong Ta’dung (JURNAL ILMIAH EDUNOMIKA, 2024)
The research objective to be achieved is to determine EPS, ROA and DER on share prices. This type of research uses a quantitative approach. The data collection technique is secondary data in the form of financial reports. Instrument testing techniques are multiple linear regression test, determinant coefficient test and hypothesis test. Data were analyzed using SPSS version 26. The results showed that partial EPS had a negative and insignificant effect on stock prices, partial ROA had a positive and significant effect on stock prices, DER had a negative and insignificant effect on stock prices. Keywords: Share Price, Earning Per Share, Return On Assets, Debt to Equity Ratio